Error concealment algorithm for entire frame loss based on optical flow estimation - CAO Ning; HU Jian-rong; MA Yin-song (Tongxin xuebao)
The whole frame loss in wireless environment and a specific and applicable solution was presented with better performance based on optical flow estimation,which was testified by experimental results.